Jesus today : experience hope through his presence - Young, Sarah, 1946- (Nashville : Thomas Nelson, 2012)
A glorious future awaits all who anchor their hope in Jesus. Reaching out with peace-filled reminders of Jesus' presence from the Word of God, these devotions will intimately, quietly connect you with Jesus, the One who meets you right where you are.
Includes index.
Keywords: Devotional literature, English; Hope -- Religious aspects -- Christianity -- Meditations; Christianity -- 21st century